Falling short of a culture of health: Planning alcohol-permitted events at a U.S. university. (30th September 2020) - Nieri, T; Webb, M; Goodwin, D; Yoo, M
Abstract: The Healthy Campus movement in the United States aims to infuse health promotion into higher education operations. We examined the extent to which event planners employ a culture-of-health approach related to alcohol consumption when planning alcohol-permitted events in a large, public university in California. We interviewed 31 event planners to assess their strategies for ensuring health and safety at the events and accommodating people in recovery from substance use disorders. We focused on events that involved faculty, staff, and graduate students. Event planners were most concerned about avoiding legal liabilities at the events, were less concerned about promoting responsible drinking among drinkers, and often failed to consider the needs of non-drinkers at the events. Their actions were informed by problematic beliefs about alcohol (e.g., people need alcohol to relax), drinkers (e.g., only undergraduate students engage in risky consumption), and people in recovery (e.g., they lack self-control). Planners over-relied on informal control to shape attendees' behavior, failing to acknowledge how contextual factors can shape individual behavior. Planners need to be educated about how to shape the event context to promote healthy behaviors, avoid exclusively focusing on preventing unhealthy behaviors and informal control, and promote better inclusion of people who don't drink. Key messages: There is fertile ground for infusing a culture of health into events in higher education. Event planners need expanded perspectives that consider context, inclusivity, and health promotion.